Ariadna spiders as bioindicator of heavy elements contamination in the Central Namib Desert. (December 2018) - Conti, E.; Costa, G.; Liberatori, G.; Vannuccini, M.L.; Protano, G.; Nannoni, F.; Corsi, I.
Highlights: Ariadna spiders were identified in Central Namib, where mining activities increased. Spider's body burden of Ag, Cd, Cu and Zn resulted higher than in sands. In contrast, Co, Cr, Ni, Pb, U and V were much lower in spider's body than in sand. All enzymes activities (CAT, GST, ChE) and MDA levels were detectable in our spiders. Ariadna spiders are bioindicator of heavy elements in the Central Namib Desert. Abstract: The present study represents the first attempt to promote Ariadna spider as bioindicator of heavy elements contamination in the central region of the Namib Desert. Various spider populations belonging to undescribed Ariadna species have been described in Central Namib gravel plains and identified as sit-and-wait predators. By spending their life in individual tunnels, Ariadna spiders resemble the behaviour of ground-dwelling spiders that are well known as bioaccumulators of heavy elements. In the present study, 60 individuals of Ariadna spiders were collected from three populations located at various distances from major mining areas of Namib Desert. Contents of fifteen heavy elements were measured in sand samples taken around spider burrows as well as in spider bodies. Several oxidative stress responses as CAT and GST, MDA levels, aside cholinergic function (Cholinesterases), were assayed. Body burden of Ag, Cd, Cu and Zn resulted significantly higher than levels measured in sand, while Co, Cr, Ni, Pb, U and V levels were one or two order of magnitude lower in spider body than in sand samples. All enzymes activities (CAT, GST, ChE) as well as MDA levels were detectable in Ariadna spiders despite lower values than other species. Though we cannot affirm that all sampled spiders belong to the same species, their enzymatic activities reflect their ability to accumulate heavy elements regardless the specific habitat features, confirming so the value of this genus as bioindicator of heavy elements in the Central Namib Desert.